The Integration of Science and Policy in Regulatory Decision-Making: Observations on Scientific Expert Panels Deliberating GM Crops in Centers of Diversity - Hokanson, Karen E.; Ellstrand, Norman; Raybould, Alan (Frontiers in Plant Science, 2018)
A perspective is shared based on three separate cases of scientific expert panels convened to consider the risks associated with gene flow in centres of diversity from a genetically modified (GM) crop to naturally occurring ‘wild’ relatives of that crop. The three cases considered were a nutritionally enhanced sorghum, an insect resistant cowpea, and a virus resistant cassava, all being developed for cultivation in Africa. Experts with relevant knowledge and experience are often called upon for risk assessments of GM crops to help clarify the available information about the crop, the introduced trait, and the environment where it will be grown. In these cases, the experts used problem formulation to identify possible adverse effects and formulate plausible scenarios that might lead to them, and then discussed what information is known in order to determine whether each of the steps in the pathway is likely or not to occur. The process of problem formulation was extremely useful to focus, facilitate, and communicate about the outcomes of these expert panel discussions. However, one important observation from all of these cases is that it is outside the remit of such experts to determine which information is necessary, ‘need-to-know’ vs. ‘nice-to-know’, in order to make a decision about the acceptable level of risk. These experiences of expert panels to inform GM crop risk assessment support the critical need for integration of science and policy for effective regulatory decision-making.